(untitled) (Journal of economic and management development research, 2026)
The Jiangsu City Football League (hereinafter referred to as "Suchao"), as a mass sports event that garnered widespread attention in 2025, has completed a value leap from a regional mass event to a national cultural tourism phenomenon, with 2.2 billion online live broadcasts and 2.43 million on-site spectators. Grounded in the theoretical framework of humanistic economics, this paper systematically investigates the intrinsic mechanism through which "traffic" is transformed into "increment" within the digital communication of Suchao. The study reveals that Suchao has constructed a triple transformation mechanism of "cultural narrative—emotional capital—symbolic consumption": deconstructing regional symbols through "memes" to achieve communication breakthrough; consolidating emotional identification via the synergy of large and small screens and user co-creation; and integrating cultural, tourism, sports, and commercial scenarios through the "ticket stubs economy," ultimately completing the value leap from traffic aggregation to economic increment. Compared with existing studies that predominantly focus on descriptive analyses of phenomena such as "Cunchao" (Village Super League) and "Harbin," the marginal contributions of this paper are as follows: first, introducing humanistic economics theory into the research of sports event communication, thereby expanding the application scenarios of this theory; second, proposing the triple transformation mechanism of "cultural narrative—emotional capital—symbolic consumption," which reveals the unique transformation logic of mass sports events distinct from professional events; third, refining the concept of "ticket stubs economy," providing a new analytical tool for traffic economy research. This "traffic-increment" transformation model elucidates the practical logic of "humanities empowering economy" for mass sports events in the digital economy era and offers an empirical sample for the theoretical construction of humanistic economics.